Factors Influencing Osseous Union Following Surgical Treatment of Bone Tumors with Use of the Capanna Technique. (20th November 2019) - Li, Jing; Chen, Guojing; Lu, Yajie; Zhu, Haodong; Ji, Chuanlei; Wang, Zhen
Abstract : Background: The Capanna technique involves the use of a vascularized fibular graft inlaid in a massive bone graft in intercalary reconstruction for diaphyseal long-bone defects caused by tumor resection. Allograft-host union time varies in different reports, and few studies have focused on the underlying factors affecting union time. The purpose of the present study was to analyze factors relevant to union time and to report complications of the Capanna technique. Methods: We identified 60 patients who underwent segmental reconstruction with use of the Capanna technique following tumor resection (in the humerus in 10 patients, the femur in 33 patients, and the tibia in 17 patients). Multivariable linear multiple regression model analysis was performed with allograft-host osseous union time as the dependent variable. Union time was evaluated on radiographs. Independent variables included age, tumor site, adjuvant treatment, a previous surgical procedure, defect length, fixation method, and fibular viability. A retrieved specimen of the composite was histologically assessed. Results: The mean defect length was 16 cm. All allografts and host bone united, with the mean time to union of 13 months (range, 6 to 27 months). Prolonged union time was associated with devitalization of the fibular graft (p < 0.001), use of chemotherapy (p = 0.031), and a previous surgical procedure (p = 0.048). Patient age (p = 0.742), amount of resection (p = 0.907), operative site (p = 0.508), and fixation method (p = 0.105) were not associated with union time. On histological analysis, we found that the allograft-host cortical junction was united by callus from both periosteum of the host bone and the fibula. Conclusions: The Capanna technique appears to be a reliable method for intercalary reconstruction with a low rate of complications. Devitalization of the transplanted fibula, chemotherapy, and a previous surgical procedure are adverse factors leading to prolonged union time. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.